Activity of biochemical biomarkers in grasshoppers Abracris flavolineata (De Geer, 1773) (Orthoptera: Acrididae: Ommatolampidinae) (Research, Society and Development, 2021)
Biochemical biomarkers are commonly used in environmental monitoring programs due to their sensitivity to certain pollutants. From this perspective, their responses can be used as indicators of environmental quality. The present study aimed to determine the activity of the catalase (CAT) and glutathione-S-transferase (GST) enzymes in grasshoppers Abracris flavolineata (De Geer, 1773) from two forest remnant areas in Serra da Jiboia (BA) and compare them between males and females. The specimens were collected at two sites in Serra da Jiboia (Bahia, Brasil), named ‘Baixa de Areia’ and ‘Baixa Grande’. The animals were actively collected in the morning using a sweep net and a 2.5 h sampling effort. In total, 160 individuals were collected, with 80 individuals from each sampling site, 50 males and 30 females. After identification, an incision was made in the lateral region of the abdomen to remove the midgut, which was used to extract the CAT and GST enzymes. The results obtained demonstrated that CAT and GST activity did not vary significantly between sampling areas. However, with regard to sex, enzyme activity was significantly higher in males (p